Renal Replacement Therapy in Acute Kidney Failure due to Rhabdomyolysis - G. Maggi; F. Quinteros Hinojosa; M. J. Villagran; E. Guasch Arévalo; F. Gilsanz Rodríguez (Case Reports in Critical Care)
Rhabdomyolysis is a syndrome caused by skeletal muscle cells destruction which can occur for many reasons, including prolonged immobilization. The main complication of the syndrome is the development of acute renal failure. Rhabdomyolysis and myoglobinuria are responsible for approximately 5% of all causes of acute renal failure in the USA. The cause of rhabdomyolysis is often multifactorial, and approximately 8–20% of such patients develop myoglobinuric acute renal failure.